Boys and their Toys: Masculinity, Class and Technology in America - Horowitz, Roger (Routledge, 2001)
Negotiating the divide between "respectable manhood" and "rough manhood" this book explores masculinity at work and at play through provocative essays on labor unions, railroads, vocational training programs, and NASCAR racing.
Keywords: Business History and gender